2021
DOI: 10.3390/electronics10080944
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Immune System for Fault Detection and Classification of Semiconductor Equipment

Abstract: Semiconductor manufacturing comprises hundreds of consecutive unit processes. A single misprocess could jeopardize the whole manufacturing process. In current manufacturing environments, data monitoring of equipment condition, wafer metrology, and inspection, etc., are used to probe any anomaly during the manufacturing process that could affect the final chip performance and quality. The purpose of investigation is fault detection and classification (FDC). Various methods, such as statistical or data mining me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The target process was silicon etching using SF 6 , O 2 , and Ar gas plasma. Previous studies have shown that small changes in plasma conditions can significantly affect the Si trench etching results for high aspect ratio [19,21,24,25]. Those studies used 20 × 20 mm 2 silicon pattern samples with an SiO 2 etch mask grown on a 300 mm silicon wafer, whereas in this study, 300 mm silicon wafers were used without a mask.…”
Section: Experiments and Data Acquisitionmentioning
confidence: 99%
“…The target process was silicon etching using SF 6 , O 2 , and Ar gas plasma. Previous studies have shown that small changes in plasma conditions can significantly affect the Si trench etching results for high aspect ratio [19,21,24,25]. Those studies used 20 × 20 mm 2 silicon pattern samples with an SiO 2 etch mask grown on a 300 mm silicon wafer, whereas in this study, 300 mm silicon wafers were used without a mask.…”
Section: Experiments and Data Acquisitionmentioning
confidence: 99%
“…A similar work has been suggested for plasma etch modeling employing a neural network with partial diagnostic data [13]. Recent works on plasma process/equipment FDC are still being actively investigated owing to the advent of machine learning (ML) and artificial intelligence (AI) [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 97%
“…It is commonly used for detecting the etching process endpoint and has been actively investigated for fault detection of plasma equipment using statistics-based modeling approaches [ 12 , 13 ]. A high-performance model can be implemented by manipulating OES data to obtain plasma information, including electron temperature and electron density [ 14 , 15 ], or by selecting radical peaks related to the process based on domain knowledge [ 16 ].…”
Section: Introductionmentioning
confidence: 99%